Association of nutritional risk index with metabolic biomarkers, appetite‐regulatory hormones and inflammatory biomarkers and outcome in patients with chronic heart failure. Issue 11 (2nd September 2014) - Gouya, G.; Voithofer, P.; Neuhold, S.; Storka, A.; Vila, G.; Pacher, R.; Wolzt, M.; Hülsmann, M.
Summary: Aims: We aimed to evaluate the association of the nutritional status by using the nutritional risk index (NRI) with metabolic and inflammatory biomarkers, and appetite‐regulatory hormones in a cohort of stable patients with heart failure (HF), and to analyse its prognostic value. Methods and results: In this prospective observational cohort study, we included 137 stable chronic HF patients (median age, 60 years; median body mass index, 27 kg/m 2 ) with optimised medical treatment. Baseline NRI of < 113 ( n  = 45) was associated with a significant increase in the levels of ghrelin (p < 0.001), peptide YY (p = 0.007), pentraxin‐3 (p = 0.001), tumour necrosis factor‐alpha (p = 0.018), adiponectin (p < 0.0001) and the N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP; p < 0.0001) compared with those in patients with NRI of ≥ 113. The NRI was found to be correlated with the homoeostasis model assessment of insulin resistance index (r = 0.444; p < 0.0001) and inversely correlated with the NT‐proBNP level (r = −0.410; p < 0.0001). The overall mortality rate was 20%. A baseline NRI of < 113 was associated with a higher risk of all‐cause mortality (log rank = 0.031). Conclusion: We propose that the NRI is a useful and easily applicable tool for the early identification of nutritional depletion in patients with chronic HF as it discriminates metabolic changes prior to the clinical manifestation of body wasting. Furthermore, poor nutritional status, represented as a low NRI, is associated with an increased incidence of death in such cases. Abstract : Linked Comment: Vincent. Int J Clin Pract 2014; 68: 1284–5 .